Effect of moringa and bagasse ash filler particles on basalt/epoxy composites - Prakash Sampath; Senthil Kumar Velukkudi Santhanam (Polímeros)
Abstract This study evaluated the effect of moringa and nano ash filler particles on mechanical, chemical corrosion and moisture absorption of basalt fiber/epoxy composites. Epoxy resin and Araldite HY951 hardener was used as matrix along with the inclusion of filler particles while the bi-directional woven basalt fiber mat was used as the reinforcement in fabricating composites using hand layup technique. Three different composites i.e. Plain BF + matrix with no filler particles, BF + matrix with 10 wt, % moringa ash and BF + matrix with 10 wt, % bagasse ash were fabricated and tested according to the ASTM standards to determine the mechanical properties and chemical corrosion resistance. According to the experimental test results, the composites with moringa ash inclusion showed better properties than the bagasse ash inclusion and with no filler added composites.